(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The bivalve Daonella Mojsisovics, 1874 is very common in the Middle Triassic pelagic facies, whereas the record of this genus from shallow water limestones is rare. In the present paper a new species of Daonella, named D. pseudograbensis, is described from the Esino Limestone, a Ladinian (Middle Triassic) carbonate platform in the central Southern Alps. The species is described from Brembana Valley, where the Esino Limestone is rather rich in bioclastic lenses yielding faunas with bivalves, cephalopods, gastropods, brachiopods, corals and calcareous algae. Daonella pseudograbensis n. sp. is based on very well preserved specimens, which are often articulated and closed, all coming from the same locality. The new species shows a narrow range of intraspecific and ontogenetic morphologic variations. It is easy distinguishable from the other species of the genus for the outline and ornamentation; it therefore differs from D. grabensis Kittl, 1912, the most similar species, for the longer anterior dorsal margin.Pdf